2022
DOI: 10.1029/2022jg006831
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Microtopography Affects Event‐Driven Stream DOC Concentrations and DOM Quality in a Forested Headwater Catchment

Abstract: Despite freshwater systems covering less than 3% of the Earth's surface, carbon fluxes from terrestrial into freshwater systems play an important role in the global carbon cycle (Battin et al., 2009;Cole et al., 2007;Raymond et al., 2013). A recent study estimated that 5.1 Pg terrestrial carbon are transported into inland waters every year (Drake et al., 2018). However, there are still many uncertainties regarding the export of carbon from terrestrial systems, which includes particular organic carbon, dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 141 publications
(200 reference statements)
0
3
0
Order By: Relevance
“…These areas at the interface between the terrestrial and aquatic ecosystems can exert an important control on stream biogeochemical cycling (Naiman & Décamps, 1997). Research in temperate and boreal regions has shown that discrete points along the riparian corridor can play a significant role in transferring both DOC (Blaurock et al., 2022; Lupon et al., 2023; Ploum et al., 2021) and DIC (Leith et al., 2015; Öquist et al., 2009) to adjacent streams. It is reasonable to expect that these findings from northern regions would also apply to tropical streams.…”
Section: Discussionmentioning
confidence: 99%
“…These areas at the interface between the terrestrial and aquatic ecosystems can exert an important control on stream biogeochemical cycling (Naiman & Décamps, 1997). Research in temperate and boreal regions has shown that discrete points along the riparian corridor can play a significant role in transferring both DOC (Blaurock et al., 2022; Lupon et al., 2023; Ploum et al., 2021) and DIC (Leith et al., 2015; Öquist et al., 2009) to adjacent streams. It is reasonable to expect that these findings from northern regions would also apply to tropical streams.…”
Section: Discussionmentioning
confidence: 99%
“…Warmer summer and early fall temperatures are favorable for the accumulation of a larger pool of available DOC (Strohmeier et al., 2013). With disrupted flow in a non‐perennial stream, DOC may be stranded in the hyporheic zone (Harjung et al., 2019), tiny pockets of stream water (Granados et al., 2020), and shallow OM‐rich soils adjacent to the stream (Blaurock et al., 2022). Summer storms occurring after disconnected conditions not only briefly reconnect channel sources but also increase hydrologic connectivity to accumulated DOC in wetter pockets of the riparian zone (Blaurock et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…With disrupted flow in a non‐perennial stream, DOC may be stranded in the hyporheic zone (Harjung et al., 2019), tiny pockets of stream water (Granados et al., 2020), and shallow OM‐rich soils adjacent to the stream (Blaurock et al., 2022). Summer storms occurring after disconnected conditions not only briefly reconnect channel sources but also increase hydrologic connectivity to accumulated DOC in wetter pockets of the riparian zone (Blaurock et al., 2022). Drying‐rewetting cycles occurring during summer and early fall then provide small flushes that gather up stored DOC, whether from in‐channel pools or more distal terrestrial sources, and stimulate new biogeochemical transformations with changing DO and redox conditions.…”
Section: Discussionmentioning
confidence: 99%